Internet-Based Experiments for EEE Education in Sudan: Opportunities and Roadmap - Sharif, Sami (University of Khartoum Engineering Journal, 2025)
This paper examines the role of internet-based technologies in rebuilding, modernizing, and sustaining electrical and electronic engineering (EEE) education in Sudan. Amid infrastructure collapse and limited resources, virtual, remote, and hybrid laboratories offer practical alternatives to traditional lab environments. The study reviews global case studies and presents a phased implementation strategy suited to Sudanese universities—beginning with virtual simulations, expanding to kit-based hybrid labs, and culminating in shared remote lab networks. A SWOT analysis identifies key enablers and risks. While challenges such as internet access and faculty training persist, online labs represent a strategic opportunity to restore and future-proof EEE education in post-conflict settings.